PENGARUH PEMBERIAN LAPISAN LEMPUNG TERHADAP PENINGKATAN LENGAS TANAH PADA LAHAN MARGINAL BERPASIR - Sudaryono, Sudaryono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Various methods for water or soil humidity conservation include the use ofchemicals (synthetic matter) and plastic or asphalt layer at certain depthunder soil profile to hold irrigation or rain water entering into the soil toprevent rapid disappearance from root zone. The present study observedthe role of fine texture soil (clay fraction) in increasing water capacity, andreleasing power of water for the need of plantation in marginal soil withsand easily pressed structure, and sensitive to water and wind erosion.The study was carried out in Glagah Coast, Kulon Progo, Yogyakarta. Theresults conclude that the addition of 10 cm of clay layer at the depth of 20-30 cm may optimally increase the humidity of sandy soil.